2019
DOI: 10.1007/s00586-019-06058-2
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficient as an indicator of spinal cord compression due to anterior atlanto-axial subluxation in rheumatoid arthritis patients

Abstract: The aim of this retrospective study was to evaluate the apparent diffusion coefficient (ADC) as a potential parameter of spinal cord damage in cervical spine instability at the atlanto-axial level in rheumatoid arthritis (RA) patients. Methods One hundred and six RA patients were included in the study. MRI examinations were performed with 1.5T scanner. The ADC was measured at six locations in the cervical spinal cord at the height of the first six cervical vertebrae (from C-1 to C-6). The ADC values were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Recently, apparent diffusion coefficient (ADC) allows the early identification of cervical cord pathologies in patients with anterior AAS and normal MRI. This parameter may be useful for spinal surgery qualification [ 34 ]. Compared to a control group of patients with osteoarthritis, there were no statistically significant differences in prevalence of spinal stenosis, cervical cord compression, cervical myelopathy, and brain stem compression between patients with RA and osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, apparent diffusion coefficient (ADC) allows the early identification of cervical cord pathologies in patients with anterior AAS and normal MRI. This parameter may be useful for spinal surgery qualification [ 34 ]. Compared to a control group of patients with osteoarthritis, there were no statistically significant differences in prevalence of spinal stenosis, cervical cord compression, cervical myelopathy, and brain stem compression between patients with RA and osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The pannus will disappear after an immobilization of the atlantoaxial segment, and no progression of the upward migration of the dens despite the unchanged systemic course of the disease during the 5year follow-up. 12 And there were no significant increase in the Redlund-Johnell index too. 16 Early atlantoaxial fusion seemed to…”
Section: Case Reportmentioning
confidence: 89%
“…Once it turns to myelopathy, 50% will die in a year. 12 In this case report, we describe a successfully managed patient with rheumatoid arthritis who developed erosive destruction of the odontoid process, anterior atlantoaxial subluxation, superior migration of odontoid, sub-axial subluxation, and cervical canal stenosis. Stenosis at level C34 that occurs due to anterior listhesis C3 to C4, which can be exacerbated by flexion-extension movements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…37,38 DWI may be also useful in detecting early spinal cord damage. New research found 39 that ADC value at the level of the 1st vertebra was significantly higher in rheumatoid patients with atlanto-axial instability than in the group without instability, despite the lack of signal changes in standard MR images (Fig. 6).…”
Section: Update In Magnetic Resonance Imagingmentioning
confidence: 94%